Hydroxyapatite and Titanium Dioxide Nanoparticles: Radiolabelling and In Vitro Stability of Prospective Theranostic Nanocarriers for 223Ra and 99mTc - Suchánková, Petra; Kukleva, Ekaterina; Nykl, Eva; Nykl, Pavel; Sakmár, Michal; Vlk, Martin; Kozempel, Ján (Nanomaterials (Basel, Switzerland), 2020)
Hydroxyapatite and titanium dioxide are widely used materials in a broad spectrum of branches. Due to their appropriate properties such as a large specific surface area, radiation stability or relatively low toxicity, they could be potentially used as nanocarriers for medicinal radionuclides for diagnostics and therapy. Two radiolabelling strategies of both nanomaterials were carried out by 99mTc for diagnostic purposes and by 223Ra for therapeutic purposes. The first one was the radionuclide sorption on ready-made nanoparticles and the second one was direct radionuclide incorporation into the structure of the nanoparticles. Achieved labelling yields were higher than 94% in all cases. Afterwards, in vitro stability tests were carried out in several solutions: physiological saline, bovine blood plasma, bovine blood serum, 1% and 5% human albumin solutions. In vitro stability studies were performed as short-term (59 h for 223Ra and 31 h for 99mTc) and long-term experiments (five half-lives of 223Ra, approx. 55 days). Both radiolabelled nanoparticles with 99mTc have shown similar released activities (about 20%) in all solutions. The best results were obtained for 223Ra radiolabelled titanium dioxide nanoparticles, where overall released activities were under 6% for 59 h study in all matrices and under 3% for 55 days in a long-term perspective.
Keywords: nanoparticles; 99mTc; in vitro stability; titanium dioxide; technetium; radium; 223Ra; hydroxyapatite; radiolabelling; theranostic